2009
DOI: 10.1063/1.3266855
|View full text |Cite
|
Sign up to set email alerts
|

Patterned electrode vertical field effect transistor fabricated using block copolymer nanotemplates

Abstract: We report the design and implementation of a vertical organic field effect transistor which is compatible with standard device fabrication technology and is well described by a self consistent device model. The active semiconductor is a film of C 60 molecules, and the device operation is based on the architecture of the nanopatterned source electrode. The relatively high resolution fabrication process and maintaining the low-cost and simplicity associated with organic electronics, necessitates unconventional f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
106
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(109 citation statements)
references
References 18 publications
1
106
1
Order By: Relevance
“…The same architecture was also more recently used for organic light-emitting transistors on plastic, 14 SiO 2 -gate transistors with carbon nanotubes for charge injection enhancement 15 and transistors based on other material combinations. [16][17][18][19] Apart from the above cited problem, the use of LiF as a gate insulator implies in high gate capacitance, which is a necessary characteristic in the conventional architecture organic FETs for the conducting channel formation. This high capacitance, however, results high RC time constant values when the device is operated, with a consequent limitation of the frequency at which such devices can be switched or modulated, so that insulator options are welcome for this structures, especially those compatible with flexible substrates.…”
mentioning
confidence: 99%
“…The same architecture was also more recently used for organic light-emitting transistors on plastic, 14 SiO 2 -gate transistors with carbon nanotubes for charge injection enhancement 15 and transistors based on other material combinations. [16][17][18][19] Apart from the above cited problem, the use of LiF as a gate insulator implies in high gate capacitance, which is a necessary characteristic in the conventional architecture organic FETs for the conducting channel formation. This high capacitance, however, results high RC time constant values when the device is operated, with a consequent limitation of the frequency at which such devices can be switched or modulated, so that insulator options are welcome for this structures, especially those compatible with flexible substrates.…”
mentioning
confidence: 99%
“…Additionally, Rossi et al [7] and Seidel et al [8] have shown that the intermediate electrode resistance can be minimized by using additional metallic or polymeric layers, respectively. There are also strategies to produce electrodes with controlled permeability like the use of sphere-lithography [15e17], co-deposition of metal and organic molecules [18], atomic layer deposition assisted nanoimprint lithography [19], random network of metallic nanowires [20], C 60 -graphene vertical heterostructures [21] or use of blockcopolymer templates [9] to obtain improved ON/OFF ratio and lower operation voltage. However, these strategies may require more complex device production steps, leading to a consequent cost rise and eliminating one of the potential advantages of the VOFETs.…”
Section: Introductionmentioning
confidence: 99%
“…2 Although many efforts have been made for improving their performance, the reported vertical organic FETs still exhibit a high operation voltage ͑Ͼ5 V͒ and non-Ohmic contact, which results in potential critical barrier for battery-powered portable applications. [7][8][9] At the same time, all researches are only focused on organic semiconductors and vertical FETs with inorganic oxide semiconductor channels are not reported.…”
mentioning
confidence: 97%